An Asymptomatic Large Anterior Sacral Meningocele in a Patient with a History of Gestation: A Case Report with Radiological Findings - Mehmet Beyazal (Case Reports in Radiology)
Anterior sacral meningocele is characterized by herniation of the meningeal sac due to a developmental bone defect in the front of a sacrum bone. It was first described in 1837. The sacral meningocele may be congenital or acquired. It is usually discovered during a rectal or pelvic examination as a cystic lesion or discovered incidentally. Most of the symptoms are due to compression on the adjacent organs. In this paper, we present a case of an asymptomatic female patient who had a pelvic cyst detected during a routine obstetric ultrasound examination. We show radiological findings of the detailed postpartum evaluation of the cyst, which led to detection of sacral agenesis, huge anterior sacral meningocele, and significant arcuate uterus.